1994
DOI: 10.1046/j.1471-4159.1994.63031021.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Brain‐Derived Neurotrophic Factor and Neurotrophin‐3 on Neurochemical and Behavioral Deficits Associated with Partial Nigrostriatal Dopamine Lesions

Abstract: Brain‐derived neurotrophic factor (BDNF) promotes the survival of dopamine (DA) neurons, enhances expression of DA neuron characteristics, and protects these cells from 6‐hydroxydopamine (6‐OHDA) toxicity in vitro. We tested the ability of BDNF or neurotrophin‐3 (NT‐3) to exert similar protective effects in vivo during chronic delivery of 6‐OHDA to the rat neostriatum. Chronic infusions of BDNF or NT‐3 (12 µg/day) above the substantia nigra were started 6 days before and continued during an 8‐day chronic intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(40 citation statements)
references
References 0 publications
1
37
0
2
Order By: Relevance
“…Our in-house comparisons indicate, however, that LY503430 provides superior protection to all these other pharmacological interventions. We have not evaluated central administration of growth factors, but, for example, GDNF is effective in both nigral and striatal 6-OHDA lesion models (Altar et al, 1992(Altar et al, , 1994Rosenbald et al, 2000). In addition, in the current studies we observed an increased level of BDNF immunoreactivity in the substantia nigra after LY503430 treatment in the 6-OHDA-lesioned animals.…”
Section: Ly503430 As a Selectivementioning
confidence: 49%
See 1 more Smart Citation
“…Our in-house comparisons indicate, however, that LY503430 provides superior protection to all these other pharmacological interventions. We have not evaluated central administration of growth factors, but, for example, GDNF is effective in both nigral and striatal 6-OHDA lesion models (Altar et al, 1992(Altar et al, , 1994Rosenbald et al, 2000). In addition, in the current studies we observed an increased level of BDNF immunoreactivity in the substantia nigra after LY503430 treatment in the 6-OHDA-lesioned animals.…”
Section: Ly503430 As a Selectivementioning
confidence: 49%
“…Many investigators have reported that glial derived growth factor (GDNF) promotes dopamine neuron survival (Tomac et al, 1995;Gash et al, 1996;Rosenbald et al, 2000), whereas other studies have shown that brain-derived growth factor (BDNF) can protect against behavioral, biochemical, and immunocytochemical changes after nigrostriatal dopamine lesions (Altar et al, 1992(Altar et al, , 1994Klein et al, 1999). A major drawback of growth factors is their large size and therefore the need to administer these molecules directly into the brain.…”
mentioning
confidence: 99%
“…Supranigral infusion of BDNF was subsequently shown to reverse behavioral and biochemical deficits induced by intrastriatal infusion of 6OHDA (Altar et al 1994). However, BDNF did not protect mesencephalic dopamine neurons from axotomy (Knusel et al 1992;Lapchak et al 1993).…”
Section: Other Neurotrophic Factors Affecting the Development Of Sn Dmentioning
confidence: 99%
“…Moreover, infusion of BDNF into the SN before or during chronic intrastriatal infusion of 6-OHDA does not prevent the loss of dopaminergic terminals in the striatum and does not protect against a partial loss of nigral dopamine neurons, but does reverse rotational behavior and augments dopamine metabolism (7). Delivery of BDNF, intracerebroventricularly or direcdy into brain tissue, shows relatively poor tissue penetration and diffusion when compared to other neurotrophins (e.g., NT-3 or NGF) (9), due in large part to the ubiquitous presence of both catalytic and non-catalytic trkB receptors throughout the brain.…”
Section: Infusion Of Bdnf Into the Sn Immediately After Transection Omentioning
confidence: 99%
“…NT-3 decreases body weight during chronic infusion periods, increases the frequency of amphetamine-induced contraversive rotational behavior, and attenuates amphetamine-induced locomotor activity (115). Infusion of NT-3 into the SN before and during a chronic intrastriatal infusion of 6-OHDA does not prevent the loss of dopaminergic terminals in the striatum and does not protect against a partial loss of nigral dopamine neurons, but does reverse rotational behavior and augments dopamine metabolism (7). Notably, infusion of NT-3 into the SN immediately after transection of the ipsilateral nigrostriatal pathway is less potent at promoting the survival of dopamine neurons than BDNF, but completely preserves TH expression (67).…”
Section: Sn Of Adult Rats (4)mentioning
confidence: 99%